The Influence of Motivation and Work Environment on Teacher Performance at SDN Boneoge, Donggala Regency - Rukhayati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The study's results simultaneously show that the independent variable, namely Motivation, justifies the first hypothesis, which states that it has a positive and significant influence on teacher performance at SDN Boneoge, Donggala Regency. This is evident from the results of the f test, obtaining a value of = 6.730 accepted with a significant level of 5% (0.00 Ë‚ 0.05) is proven. Work motivation positively affects teacher performance at SDN Boneoge, Donggala Regency. This is not established from the test results. T obtained ngs significant level of 2.303 5% (0.003 Ë‚ 0.05 ) and was accepted. This means the higher the teacher's work motivation, the more performance will increase. The work environment positively affects teacher performance at SDN Boneoge, Donggala Regency. This is not proven from the results of the t-test obtained value 3.030 at a significant level of 5% (0.005 Ë‚ 0.05), and accepted. This means the higher the teacher's work environment, the more performance will increase.